2017
DOI: 10.1684/ejd.2017.3086
|View full text |Cite
|
Sign up to set email alerts
|

Microwave therapy for cutaneous human papilloma virus infection

Abstract: Background: Human papilloma virus (HPV) infects keratinocytes of the skin and mucous membranes, and is associated with the induction of cutaneous warts and malignancy. Warts can induce significant morbidity and disability but most therapies, including cryotherapy, laser, and radiofrequency devices show low efficacy and induce discomfort through tissue destruction. Microwaves are readily capable of passing through highly keratinised skin to deliver energy and induce heating of the tissue in a highly controllabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(49 citation statements)
references
References 28 publications
(28 reference statements)
6
41
2
Order By: Relevance
“…In future studies, adopting a stepwise overlapping delivery of treatment across the whole surface of the AK might lead to higher rates of complete resolution. This approach has been used successfully for plantar warts . Seven per cent of untreated AKs had spontaneously resolved by visit 11, which is similar to that reported in other studies and demonstrates the importance of an internal control.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In future studies, adopting a stepwise overlapping delivery of treatment across the whole surface of the AK might lead to higher rates of complete resolution. This approach has been used successfully for plantar warts . Seven per cent of untreated AKs had spontaneously resolved by visit 11, which is similar to that reported in other studies and demonstrates the importance of an internal control.…”
Section: Discussionsupporting
confidence: 83%
“…Microwave therapies are established within oncology for ablative treatment of internal malignancies . Microwave energy has shown promise in the treatment of recalcitrant plantar viral warts . This study used a CE‐marked microwave medical device (Swift ® Microwave Tissue Ablation System, Emblation Ltd, Alloa, UK).…”
mentioning
confidence: 99%
“…Preliminary studies of human skin explants exposed to low-level microwave energy suggested that increased danger signalling in keratinocytes, including induction of HSP70, may be the critical pathway for cutaneous wart resolution. Microwave-treated keratinocytes were able to induce dendritic cell activation (CD80, CD86, CD40) and enhancement of anti-HPV responses by CD8+ T cells [ 12 , 13 ]. This case study represents an exciting additional therapeutic option for treatment of recalcitrant cutaneous warts.…”
Section: Discussionmentioning
confidence: 99%
“…In eqs. (14), (15) The final solution for the secondary field inside the sphere and in particular for the total pressure is obtained to be:…”
Section: The Field Expression Inside the Sphere Rmentioning
confidence: 99%
“…It is observed that under physiological conditions of salinity and acidity, virus capsid assembly requires the presence of genomic material that is oppositely charged to the core proteins 10 . Furthermore, few researchers have focused their research on the possibility of inducing photon-phonon interactions 11 in virions, which are the virus causing infections 12,13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%